The role of Box A of HMGB1 in producing γH2AX associated DNA breaks in lung cancer - Sirapat Settayanon; Pithi Chanvorachote; Apiwat Mutirangura (Scientific Reports)
Abstract An ideal chemotherapeutic agent damages DNA, specifically in cancer cells, without harming normal cells. Recently, we used Box A of HMGB1 plasmid as molecular scissors to produce DNA gaps in normal cells. The DNA gap relieves DNA tension and increases DNA strength, preventing DNA double-strand breaks (DSBs). Since the formation of HMGB1-produced DNA gaps in cancers may differ from normal cells, the outcome of introducing Box A into cancer cells may be different. We demonstrated that in lung cancer cells, γH2AX foci and histone modification associating DSBs were produced by Box A. We transfected Box A plasmid into lung cancer cell lines to overexpress Box A and evaluated the expression levels of γH2AX foci and other DNA damage response (DDR) signaling cascade markers, including ATM, ATR, and p53. Then, we demonstrated the downstream effects of DSBs on lung cancer, lowering cell proliferation, decreasing cell migration, and promoting apoptosis. Thus, Box A in lung cancer promoted the opposite outcome to normal cells by breaking cancer DNA.